The investigation of PVD coating, cryogenic lubrication and ultrasonic vibration on tool wear and surface integrity in manufacturing processes - Sulaiman, Mohd Hafis; raof, Natasha A.; Dahnel, Aishah Najiah (Malaysian Tribology Society (Mytribos), 2021)
Lubricants are harmful to human health and the environment. However, it is the only effective method to reduce friction and to prevent tool wear, leading to a highquality surface. This paper presents the development and testing of environmental-friendly tribology systems in manufacturing processes – metal forming and machining. PVD coatings, cryogenic lubrication and ultrasonic vibration were introduced to replace the use of oil lubrication in manufacturing processes, and investigated on experimental works of reciprocating rig, sheet-metal forming, turning and drilling with different process parameters, ie. lubrication conditions and speeds. Combating friction and tool wear with potential tribology systems like the PVD coatings, cryogenic lubrication and ultrasonic-assisted technique have led to positive results to improve lubrication, thereby delay tool wear progression.